Health risk assessment of instant noodles commonly consumed in Port Harcourt, Nigeria - Charles, Iniobong A.; Ogbolosingha, Atieme J.; Afia, Inimfon U. (Springer, 2017)
The current study investigated the levels of some heavy metals [Lead (Pb), Arsenic (As), Nickel (Ni), Mercury (Hg), Copper (Cu), Cadmium (Cd), Aluminium (Al) and Chromium (Cr)] and Polycyclic Aromatic Hydrocarbons (PAHs) in six brands of instant noodles (CFN, GFC, NGP, GAA, CUN and FCS) commonly consumed in Port Harcourt, Nigeria. Risks of consumption of contaminated noodles were also assessed. Heavy metals content and PAHs were determined using Flame Atomic Absorption Spectrophotometer (AAS) and Gas Chromatography (GC), respectively. Concentration of heavy metals as Pb, Ni, Cu, Al and Cr were detected while As, Hg and Cd were not detected in noodles. High average concentration (mean ± SD mg/kg) of Pb were observed in brands CFN (3.163 ± 0.21) and GFC (1.022 ± 0.08) which were significantly higher (P≤0.05) than in NGP (0.043 ± 0.15) and GAA (0.276 ± 0.18), although all were above WHO permissible limits (0.025 mg/kg). Target Hazard Quotient and Hazard Index for Pb were >1 in brands CFN and GFC indicating unacceptable risk. Results of PAHs showed brands had total PAHs (mg/kg) in the order: CFN >CUN >GAA >NGP >FCS > GFC. Although Carcinogenic Risks associated with these noodles are within permissible range, consumption of CFN and GFC could pose greater health risk to consumers. Long term consumption of brands CUN, CFN and GAA may have higher probability of carcinogenesis among consumers. We therefore recommend more diligent regulatory policies and monitoring by relevant Government agencies (WHO, NAFDAC, CPC and SON) to ensure wholesome noodles get to consumers.